Social media marketing - Sedley, Richard (Henry Stewart Talks, 2010)
Introduction to social media, Key challenges to marketing and engagement, Using reciprocity, Social media planning framework, Social technographic profiling, Using social proof, Community ROI, Using existing social networks, Classical networking theory, Facebook marketing, Setting up your own community, Storytelling, Crowdsourcing, Content creation and sharing, Decoying, Atomisation, Micro-blogging (Twitter etc.), Using a simplicity framework, Monitoring and measurement framework, Handling a storm